Relation between job strain and myocardial infarction: a case-control study. Issue 5 (1st May 1999) - Netterstrøm, B; Nielsen, F E; Kristensen, T S; Bach, E; Møller, L
Abstract : OBJECTIVES: To study the influence of different job related and socioeconomic factors for development of myocardial infarction (MI). METHOD: The study was a case-control study of 76 male wage earners who had been admitted to hospital with MI. As a control group 176 male wage earners not admitted to hospital who were residents of the same county were used. Both groups were interviewed with an extensive questionnaire on job related conditions. Several indices on job related psychosocial factors were established in accordance with Karasek's job strain model as well as the extension of the model, the isostrain model. RESULTS: The most significant findings were consistent with Karasek's job strain model in that mean with a high degree of demand combined with a low degree of control at work had a significantly increased odds ratio (OR) 95% confidence interval (95% CI) of 2.1 (1.2 to 3.8) for MI after adjustment for age compared with men with a low degree of demand and a high degree of control at work. Further adjustment for smoking, socioeconomic status, employment sector, job category, and social network did not affect the OR substantially (OR 2.3 (1.2 to 4.4)). Other factors significantly associated to MI were job category (blue collar workers v white collar workers, OR 2.8 (1.6 to 5.8)), and employment sector (private v public, OR 3.1 (1.8 to 6.1)). CONCLUSIONS: Thus, the study confirmed the job strain model as well as the well known association between socioeconomic status and risk of MI, whereas the finding of an increased risk among employees in the private sector has not previously been described.